Divorce Outside the Court from the Perspective of Islamic Legal Philosophy Regarding Legal Certainty and Protection of Women's and Children's Rights - Allysa Dhini Rizalde; Budi Abdullah; Munaf Andri Revanda Sembiring; M. Rama Dhanu Jupri; Alwi Saparizhan; M. Habib Al-Muqtadir; Syerli Klara Larasati Boru Manalu (Civiliza Publishing, 2026)
This study examines out-of-court divorce from the perspective of Islamic legal philosophy, focusing on legal certainty and the protection of women’s and children’s rights. Out-of-court divorce remains common in Indonesian society and is often conducted solely through the husband’s declaration without a judicial process in the Religious Court. This practice creates legal problems concerning the status and rights of women and children after divorce. This research aims to analyze divorce in Islamic family law and Indonesian positive law and to examine the impact of out-of-court divorce on justice and legal protection. The study uses a qualitative method with a library research approach. Data were collected from the Qur’an, Hadith, laws and regulations, the Compilation of Islamic Law, books, journals, and related literature. Data analysis employed a qualitative descriptive method using the perspective of Islamic legal philosophy. The findings reveal that Islamic family law permits divorce only as a last resort and requires responsibility toward women’s and children’s rights. Indonesian positive law also stipulates that divorce is legally valid only through court proceedings to ensure legal certainty and legal protection. Out-of-court divorce often results in the loss of legal certainty, neglect of maintenance rights, uncertainty in child custody, and social and psychological impacts on women and children. From the perspective of Islamic legal philosophy, court-based divorce procedures support justice, legal certainty, and public benefit.